The Struggling State - Riggan, Jennifer (Book collections on Project MUSE., 2016)
'The Struggling State' explores Eritrean's disillusion with a government that permanently conscripts the vast majority of its citizens into the military, and examines teacher's paradoxical roles as educators who are trying to create a bright and peaceful future for the nation while situated to shuttle their students into the military.